Dismantling of Institutionalization and State Policies as Guarantors of Food Security in Venezuela: Food Safety Implications - Hernández, Pablo; Carmona, Andrés; Tapia, Maria S.; Rivas, Siloyde (Frontiers in Sustainable Food Systems, 2021)
Historically, Venezuela was recognized as a country with solid government food safety policies, science-based legislation, clear national food security goals, strict standards for domestic food production and imports, and a system of institutions committed to ensure safety and quality along each step of the food chain. The Ministry of Sanitation & Social Welfare, the National Institute of Hygiene and the National Institute of Nutrition were created in 1936, 1938 and 1949, respectively. Progress was resounding in terms of control of tropical maladies, fight against hunger and malnutrition, and promotion of food security and safety. The National Institute of Hygiene set the standards for food and drug surveillance. The National Codex Alimentarius Committee was officially created in 2001. Nowadays the situation has dramatically deteriorated. A strong dependence on food imports -that in 2013 covered 65% of the necessary caloric intake of the population-, an avalanche of food imports facilitated by the Government at a preferential exchange rate, and by an Economic Emergency Decree, resulted in transitory regulations and laxity in procedures and compliances with protocols, as well as in corruption. Although the economic crisis got worse since 2012, leading to drastic drops of food imports, the Government increased the import of basic foods for social programs. These imports were usually unsuitable to Venezuelan cultural patterns and/or did not meet nutritional composition and safety standards. In 2016, the Government allocated enormous efforts and resources to the implementation of a food distribution program: The Local Supply and Production Committee (CLAP). The objective of this work is to describe, through the Venezuelan case, how the food security infrastructure of a country can be dismantled. We address: (1) the deficient application of quality, hygiene and food safety standards in our country; (2) the irregularities found in the food security of imported products (corn flour, powdered milk, rice, tuna, etc.) and (3) the impact on Venezuelan consumers in situation of vulnerability and lack of protection in terms of food safety and security.